2018
DOI: 10.2478/msp-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured device based on coated ZnO layer as a window in solar cell applications

Abstract: This work highlights some physical properties related to the influence of aluminum, tin and copper incorporation on nanostructured zinc oxide (ZnO:M; M:Al, Sn and Cu) thin films prepared by ultrasonic spray pyrolysis technique (USP) on glass substrate at 350±5°C. For the as-grown layers, M-to Zn-ratio was fixed at 1.5 %. The effects of metal doping on structural, morphological, optical and electrical properties were investigated. X-ray diffraction pattern revealed that the as-prepared thin films crystallized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…By investigation of the transmittance and reflectance variations versus photon wavelength, we can estimate the optical band gaps of films. The reports shown that the variations of d T/ d λ and d R/ d λ exhibits peaks which their centres can be related to the gap energy 24 . The curves of d T/ d λ and (d R/ d λ ) versus wavelength were plotted Figures 7(A) and (B).…”
Section: Resultsmentioning
confidence: 99%
“…By investigation of the transmittance and reflectance variations versus photon wavelength, we can estimate the optical band gaps of films. The reports shown that the variations of d T/ d λ and d R/ d λ exhibits peaks which their centres can be related to the gap energy 24 . The curves of d T/ d λ and (d R/ d λ ) versus wavelength were plotted Figures 7(A) and (B).…”
Section: Resultsmentioning
confidence: 99%
“…transmission average value is in the [80-85]% range [7-9, 13, 21, 47] in the visible spectrum region with some works recently report transmittance as high as 95 % for layers of thickness below 30 nm elaborated using a custom made spray pyrolysis and CVD system [10] and 90% for ultrasonic spray pyrolysis elaborated layers [12]. An annealing step can increase the transmittance beyond 90 % as shown in [48].…”
Section: Tablementioning
confidence: 99%
“…Elaboration techniques used for the growth of ZnO thin films are mainly based on reactive sputtering [1,2], pulsed laser deposition [3,4], sol-gel [5], molecular beam epitaxy [6], and spray pyrolysis [7][8][9][10][11][12]. The improved technique of ultrasonic spray pyrolysis allows for a better control of the deposition compared to conventional pneumatic spray systems.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for an ideal material, the transmission for wavelengths less than (E) is zero. 33 The real and imaginary parts of the dielectric constant σ 1 and σ 2 can be used to calculate spectral behavior of the optical conductivity according to the following relations 34,35 :…”
Section: Scanning Electron Microscope Images (Sem)mentioning
confidence: 99%